«Захист» та«охорона»: теоретичні аспекти юридичних термінів - Булавіна, С.; Bulavina, S.; Давидова, Т.; Davydova, T. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті розглядається сутність юридичних термінів, які широко застосовуються вітчизняним законодавцем: «захист» та «охорона». На основі етимологічного та термінологічного аналізу та дослідження поглядів на поняття та терміни науковців з різних галузей права зроблено висновок щодо їх нетотожності. «Охорона» і «захист» відрізняються за часовими межами застосування. Охорона діє постійно, як превенція у тому числі, а захист– в результаті порушення прав та обов’язків. Розрізняються вони і за інструментарієм, що застосовується. Охорона характеризується більш широким переліком заходів– ідеологічних, економічних, правових тощо, у той час як захист– це використання суто правових методів. The article considers the terms «protection» and «security» to reveal the legal terminology issues functioning. The authors, having analyzed many scientific approaches to the interpretation of these terms, concluded that although the problem is not new, it is still under active scientific debate. Analysis of the terms content in the texts of normative legal acts gave grounds to state that the legislator uses the terms «security» and «protection» as identical. There are two main approaches to the problem in the scientific literature. Some scientists believe that these terms are synonymous,while others distinguish them by various criteria.The authors agree with the second group of researchers, concluding that «security» and «protection» are not identical in their content, functions and time frame. The «protection» of rights shall prevent violations of rights and duties, and «security» is aimed at restoration of rights and obligations or compensation for the violation of the rights. Together they guard the process of ensuring, guaranteeing and securing rights. Protection is characterized by a broad list of measures – ideological, economic, legal, etc., while security focuses on just the use of legal methods.
«Protection» and «Security»: Theoretical Aspects of the Legal Terms
Keywords: захист; охорона; охоронна функція права; юридичний термін; термінологічний аналіз; protection; security; protective function of law; a legal term; terminological analysis